2017
DOI: 10.1021/acs.iecr.7b01598
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Pt–Sn/SBA-15 Catalyst Prepared by Direct Reduction for Ethylbenzene Dehydrogenation: Effects of Sn Addition

Abstract: A series of Pt−Sn/SBA-15 catalysts (Sn/Pt nominal ratios: 0−3) prepared by direct reduction were applied to ethylbenzene dehydrogenation to styrene. The characterization by X-ray diffraction, X-ray absorption fine structure, CO adsorption, transmission electron microscopy, and X-ray photoelectron spectroscopy revealed the formation of highly dispersed and stable Pt−Sn alloy particles [Pt x Sn y (x/ y ≥ 3) and Pt−Sn alloys having Sn-rich surfaces] on SBA-15. Nonalloyed Sn existed as highly dispersed SnO 2 . 1Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…As shown in Figure 7, the SR catalysts showed the first peak at 417-454 • C, and the second peak occurred at 482-503 • C during coke oxidation. It has been reported [24] that the first peak near 417 °C can be attributed to coke combustion on either Pt or Pt-Sn alloy sites, whereas the second peak near 494.4 °C is due to the "drain-off'" effect. Here, drain-off is the case of the coke on metal sites migrating to the oxide support.…”
Section: Dta Analysismentioning
confidence: 99%
“…As shown in Figure 7, the SR catalysts showed the first peak at 417-454 • C, and the second peak occurred at 482-503 • C during coke oxidation. It has been reported [24] that the first peak near 417 °C can be attributed to coke combustion on either Pt or Pt-Sn alloy sites, whereas the second peak near 494.4 °C is due to the "drain-off'" effect. Here, drain-off is the case of the coke on metal sites migrating to the oxide support.…”
Section: Dta Analysismentioning
confidence: 99%
“…Peaks at 39 • and 45.5 • correspond to Pt 3 Sn alloy phase, whereas peaks at 41.7 • and 44 • in 2θ value correspond to the PtSn alloy phase [14,20]. Further, it was also reported that the Pt 3 Sn alloy phase was only formed at Pt/Sn molar ratios greater than 1 [14]. In the current experimental studies, the nominal Pt/Sn molar ratio was 0.4.…”
Section: Xrd Analysismentioning
confidence: 46%
“…For PtSn alloys, the characteristic peaks must be between 36 • and 48 • in 2θ value [30,33]. Peaks at 39 • and 45.5 • correspond to Pt 3 Sn alloy phase, whereas peaks at 41.7 • and 44 • in 2θ value correspond to the PtSn alloy phase [14,20]. Further, it was also reported that the Pt 3 Sn alloy phase was only formed at Pt/Sn molar ratios greater than 1 [14].…”
Section: Xrd Analysismentioning
confidence: 96%
See 2 more Smart Citations